Microbial Diversity and Physicochemical Characteristics of the Maotai-Flavored Liquor Fermentation Process - Dai, Yijie; Tian, Zhiqiang; Meng, Wangni; Li, Zongjun (Journal of nanoscience and nanotechnology, 2020)
The grains fermented in Maotai-flavored liquor can be classified into two groups: high-temperature fermented grains generated by stacking and grains fermented in pits. The Maotai-flavor making process enriches a special microbiota from the fermented grains, which makes related studies more difficult. The use of modern molecular techniques to detect and analyze diversity and changes in total bacterial (16S rRNA sequencing) and fungal (internal transcribed spacer (ITS) sequencing) counts have helped to overcome the shortcomings of traditional technological research. The total RNA extracted by Fe₃O₄-SiO₂ nanoparticles was retrieved into DNA by MagBeads Total RNA Extraction Kit. However, discrepancies exist in the microbial community structures at different fermentation periods. Dominant bacteria include , and species and dominant fungi include , and species. Analyses of the enzymatic activity of samples at different fermentation stages have revealed that some existing bacilli influence amylase activity. Here, to investigate flavor changes during each fermentation round, the liquor quality at all rounds was comprehensively assessed based on the corresponding physicochemical properties, which were summarized by sensory evaluation. These results suggested that the liquor quality in the third, fourth, and fifth fermentation rounds was superior.